Optimasi gelling agent dan humektan dalam formula gel antioksidan ekstrak daun pepaya (Carica papaya Linn.) menggunakan metode simplex lattice design - Pratiwi, Puspa Dwi; Gusti, Diah Riski; Angraini, Resti Indah (Journal of Pharmaceutical and Sciences, 2023)
Papaya leaf (Carica papaya L.) have very strong antioxidant activity with IC50 value 21.08 ppm. C. papaya L. leaf can be formulated in gel preparation. The physical properties of gel and its effectiveness as an antioxidant can be affected by excipients, so it is necessary to optimize the formula. The aims of this research were to find the concentration of sodium carboxy methyl cellulose (Na-CMC) as gelling agent and glycerin as humectant to get optimal formula with the best physical properties and measure its antioxidant activity. Simplex lattice design (SLD) method was chosen for formula optimization with Na-CMC range 0.5-4% and glycerin 10-13.5%. The optimal formula was determined based on pH value, spreadability, stickiness and viscosity then determined for antioxidant activity using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The results of this research were optimal formula with Na-CMC concentration 1.853% and glycerin 12.147%. The antioxidant activity of the optimal formula was decreased from the extract activity, with an IC50 value 21.08 ppm (very strong) to 61.70 ppm (strong). It can be concluded that the optimal formula for papaya leaf (C. papaya L.) extract gel preparation can be obtained with combination of Na-CMC and glycerin using the SLD method with strong antioxidant value.